PENGARUH PERMAINAN PETANQUE KIDS TERHADAP PERKEMBANGAN MOTORIK KASAR SISWA SEKOLAH DASAR - Ferry Ahmad Ardiansyah; Nurhasan, Nurhasan; Nurkholis, Nurkholis (Jurnal Porkes, 2024)
The purpose of this study was to examine the effect of petanque kids games on gross motor development of elementary school students. Petanque kids games have great potential in supporting the development of motor and social skills of students. This type of research is quasi-experimental with the method of one grub prestest posttest desaign using motor ability instruments, Population as many as 36 students aged 9 - 11 years at Balongsari 4 Mojokerto State Elementary School. The data analysis technique used descriptive analysis and statistical analysis with the help of the SPSS 29 program. The results showed that there was a significant influence between the pretest posttest results with a Sig value. > 0.05 and there was an increase between the pretest posttest results of the pretest posttest speed test increased by 6.31%, the pretest posttest agility test increased by 11.54%, the prestest posttest coordination test also increased by 23.85% while the balance also increased from prestest posttest by 45.50%. So it can be concluded that there is a difference between the pretest posttest which means that there is an effect of petanque kids games on the gross motor development of elementary school students.